Microbial community composition and metabolic potential during a succession of algal blooms from Skeletonema sp. to Phaeocystis sp. - Zhu, Jianming; Tang, Si; Cheng, Keke; Cai, Zhonghua; Chen, Guofu; Zhou, Jin (Frontiers in Microbiology, 2023)
Elucidating the interactions between algal and microbial communities is essential for understanding the dynamic mechanisms regulating algal blooms in the marine environment. Shifts in bacterial communities when a single species dominates algal blooms have been extensively investigated. However, bacterioplankton community dynamics during bloom succession when one algal species shift to another is still poorly understood. In this study, we used metagenomic analysis to investigate the bacterial community composition and function during algal bloom succession from Skeletonema sp. to Phaeocystis sp. The results revealed that bacterial community structure and function shifted with bloom succession. The dominant group in the Skeletonema bloom was Alphaproteobacteria, while Bacteroidia and Gammaproteobacteria dominated the Phaeocystis bloom. The most noticeable feature during the successions was the change from Rhodobacteraceae to Flavobacteriaceae in the bacterial communities. The Chao1 richness and Shannon diversity indices were significantly higher in the transitional phase of the two blooms. Metabolic reconstruction of the metagenome-assembled genomes (MAGs) showed that dominant bacteria exhibited some environmental adaptability in both blooms, capable of metabolizing the main organic compounds, and possibly providing inorganic sulfur to the host algae. Moreover, we identified specific metabolic capabilities of cofactor biosynthesis (e.g., B vitamins) in MAGs in the two algal blooms. In the Skeletonema bloom, Rhodobacteraceae family members might participate in synthesizing vitamin B1 and B12 to the host, whereas in the Phaeocystis bloom, Flavobacteriaceae was the potential contributor for synthesizing vitamin B7 to the host. In addition, signal communication (quorum sensing and indole-3-acetic acid molecules) might have also participated in the bacterial response to bloom succession. Bloom-associated microorganisms showed a noticeable response in composition and function to algal succession. The changes in bacterial community structure and function might be an internal driving factor for the bloom succession.